Nature and extent of perceived stigma among epileptics in Pakistan - Khalil, Rehana; Gul, Saadia; Naeem, Zahid (International Journal of Research in Medical Sciences, 2016)
Background: Epilepsy is one of the oldest disorders known to mankind. Often the social stigma (whether a “felt” stigma or an “enacted” stigma) attached to epilepsy is a greater handicap to the person with epilepsy compared to the disability associated with seizures or the side-effects from medications. The aim of this study was to explore the perceived sigma and discrimination among epileptics of Karachi, Pakistan. Methods: A descriptive cross sectional study was conducted in Karachi, Pakistan in the year 2016. A standardized pretested semi-structured questionnaire was completed by 120 epilepsy patients selected through purposive sampling from Department of Neurology, Jinnah Postgraduate Medical Centre. Informed verbal consent was obtained prior to the interview. The data were analysed using IBM SPSS Statistics version 22 and Microsoft excel. Results: The average age of the sample participants was 18-50 years. Almost two third (68%) of the respondents were male. More than half (55%) of the sample was educated up to matriculation. Among them 28.5% were married. Three fifth (60%) of participants were unemployed. More than half (60%) of the respondents reported discrimination in educational opportunities and three fourth (78.5%) in job opportunities. Results indicated that (75%) participants encountered social problem like being discriminated (30%), or segregated (11%) in performance of daily tasks and were avoided (58.8%) to get marry more often with the belief that people with epilepsy are infectious. Conclusions: The study concludes that there is significant perceived stigma among epileptics living in a big metropolitan city of a developing country. The nature of stigma includes discrimination in education, marriage and job opportunities. There is a need for public awareness programmes to address this ignored facet of epilepsy, since it has both medical as well as social implications.